PERBEDAAN DAYA HAMBAT EKSTRAK DAUN SISIK NAGA (Drymoglossum piloselloides Linn.) TERHADAP BAKTERI Propionibacterium acne DENGAN Shigella dysentriae - Wenti Dwi Febriani; Dwi Wahyuni; Iis Nur Asyiah (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2015)
Propionibacterium acne and Shigella dysentriae is a species of bacteria that cause inflammation. Diseases that cause acne are often caused by a bacterial infection, one of which is the bacteria Propionibacterium acne. While inflammatory bowel disease caused by a bacterial infection Shigella dysenteriae. Both are bacteria that cause inflammation. One of the plants that have the potential as an alternative antibacterial is leaf dragon scales (Drymoglossum piloselloides Linn). Inhibition of leaf extracts dragon scales (Drymoglossum piloselloides Linn) against Propionibacterium acne bacteria significantly affect the significance value of 0,000. While the dragon scales leaf extract (Drymoglossum piloselloides Linn) against Shigella dysenteriae bacteria significantly affect the significance value of 0,000. Minimal Inhibitory Concentration (MIC) which is able to inhibit the bacteria Propionibacterium acne is 0,8% with a mean inhibition zone of 0,26 cm. While the Minimal Inhibitory Concentration (MIC) which is able to inhibit the bacteria Shigella dysenteriae is 0,6% with a mean of 0,15 Keywords: Propionibacterium acne, Shigella dysentriae, Drymoglossum piloselloides Linn., acne bacteria